DEVELOPMENT AND VALIDATION OF UV-SPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF CLENBUTEROL HYDROCHLORIDE IN BULK AND PHARMACEUTICAL FORMULATION - KANKURE, SUSHMITA; KALSHETTI, MALLINATH; PATIL, RAVIKANT (International Journal of Current Pharmaceutical Research, 2020)
Objective: The objective of the present work is to develop a simple, rapid, economic UV spectrophotometric method for quantification of clenbuterol hydrochloride in bulk and pharmaceutical formulation as per ICH guidelines. Methods: A UV spectrophotometric method has been developed using water as solvent to determine the Clenbuterol hydrochloride in bulk and pharmaceutical dosage formulation. The λmax of Clenbuterol hydrochloride in water was found to be 242 nm. Results: The drug was proved linear in the range of 10-50μg/ml and exhibited good correlation coefficient (R2 = 0.9987) and excellent mean recovery (98-100%). The %RSD for intra-day and inter-day precision was found to be 0.053997676 and 0.359081556 respectively. The LOD and LOQ of clenbuterol hydrochloride was found to be 3.704448 and 11.2256 respectively. This method was successfully applied to clenbuterol content in marketed brands and the results were in good agreement with the label claims. Conclusion: The method was validated for linearity, precision, repeatability and reproducibility. The obtained results proved that the method can be employed for the routine analysis of clenbuterol in bulks as well as in commercial formulations.